Raised Serum Adenosine Deaminase Level in Nonobese Type 2 Diabetes Mellitus - Vineet Kumar Khemka; Debajit Bagchi; Arindam Ghosh; Oishimaya Sen; Aritri Bir; Sasanka Chakrabarti; Anindita Banerjee (The Scientific World Journal)
The role of inflammation being minimal in the pathogenesis of type 2 diabetes mellitus (T2DM) in nonobese patients; the aim of the study was to investigate the role of adenosine deaminase (ADA) and see its association with diabetes mellitus. The preliminary case control study comprised of 56 cases and 45 healthy controls which were age and sex matched. 3 mL venous blood samples were obtained from the patients as well as controls after 8–10 hours of fasting. Serum ADA and routine biochemical parameters were analyzed. Serum ADA level was found significantly higher among nonobese T2DM subjects with respect to controls (38.77±14.29 versus 17.02±5.74 U/L; P<0.0001). Serum ADA level showed a significant positive correlation with fasting plasma glucose (r=0.657; P<0.0001) level among nonobese T2DM subjects, but no significant correlation was observed in controls (r=-0.203; P=0.180). However, no correlation was observed between serum ADA level compared to BMI and HbA1c levels. Our study shows higher serum ADA, triglycerides (TG) and fasting plasma glucose (FPG) levels in nonobese T2DM patients, and a strong correlation between ADA and FPG which suggests an association between ADA and nonobese T2DM subjects.